(3GdJYhjV Yf GdJCNjQ aj GdhaGA HGdJRGe fbOj aj GdJTQjYGJ GdYQHjI ebGQfG HCMcGe GdTQjYI GdESdGejI (B/ s - (3hLOj YHO GdhGMO Ydj YHO GdhGMOs; (3Ydj MSjf fLjOg (B: s; (3jhSa bGSe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1997)
(3JHOC GdQSGdI HaUd JegjOj Yf WQb JbOjQ GdJYhjV, Ke JfbSe Edi KdGKI CHhGH; MK jJfGhd GdHGH GdChd GdJYhjV GdbGfhfj Yf GdJCNjQ aj GdhaGA HGdJRGe fbOj (B((3ahGFO GdJCNjQ(B) (3aj GdJTQjYGJ GdYQHjI, hGdHGH GdKGfj Yf ehbY GdahGFO ef GdQHG aj GdTQjYI GdESdGejI, hCNjQG GdHGH GdKGdK Yf BKGQ Gdabg GdESdGej Ydi eHOC GdJYhjV Yf GdJCNjQ aj GdhaGA HGdJRGe fbOj aj GdJTQjYGJ GdYQHjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1997.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B471 - 486s
Keywords: (3GdTQjYI GdESdGejIs; (3GdJfajP GdGNJjGQj s; (3GdJfajP GdELHGQj s; (3GdJfajP GdYjfjs; (3GdJCNjQ aj GdhaGA s; (3GdJfajP HWQjb GdJYhjV s; (3JMQje GdQHG s; (3Mb GdMHS s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs